Stock market prediction using time series analysis - Hira, Farhan Islam; Maruf, Mazharul Ferdous; Hossain, Afzal (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.